México: Post-Revolution, Nationalism and Inmigration Policy - Rebolledo Kloques, Octavio Bernardo (2017)
In this article, we examine the influence of the nationalistic ideology that emerged from the Mexican Revolution in 1910 as a way of understanding the role and presence of foreigners in the new model of a nation that was to be constructed.The defensive Nationalism that was strengthened by the outbreak of the revolution, limited the influence of the flow of immigration. The emergence of the doctrine of ‘Mestizaje’ sustained a conceptual framework in which latent ethnic and racial biases eventually supported the immigration policy adopted by the government in the post-revolutionary period.The Mexican people assumed the leading and exclusive role in the effort to create this new societal project, while the participation of foreigners was excluded from it.